Pengaruh Media Simulasi terhadap Keterampilan Berpikir Kritis pada Konsep Fluida Statis - Nindya Novianti; Erina Hertanti; Taufiq Al Farizi (Department of Physics Education, Universitas Mataram, 2019)
This research aim is to investigate the impact of simulation media toward critical thinking skill in static fluid concept. The research was conducted during 28 January 2019 until 13 February 2019 in SMAN 10 South Tangerang. The purposive sampiling technique was adjusted to determine subject which consist students role of XI IPA 2ÃÂ as experiment class and XI IPA 1 as control class. The research used quasi experiment method due to nonequivalent control group design. The data were collective by 10 essays test and questionnaire and Mann Whitney to analyse the accpetance of hypothesis. Thus, the result of postest score who learn using simulation media was significant (angka signifikan) effected toward critical thinking skill. In addition,ÃÂ the N-Gain result indicated student performance ofÃÂ experiment class was higher improvement than control class. However, learning using simulation media got best category resulting 86% percentageÃÂ from student response questionnaire.